2010
DOI: 10.4103/0019-5359.98961
|View full text |Cite
|
Sign up to set email alerts
|

Acute buried bumper syndrome: An endoscopic peg tube salvage approach

Abstract: Acute buried bumper syndrome is an uncommon complication of percutaneous endoscopic gastrostomy (PEG) tube placement. If not recognized and treated appropriately, it can lead to serious complications including death. We report a case of an acute buried bumper syndrome, successfully managed with PEG tube repositioning through the original tract, without the need of replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…BBS is an unusual complication with an estimated incidence ranging from 0.3 to 2.4% [ 14 , 15 , 16 ]. It can be manifested with minor complications such as feeding intolerance, peristomal leak, pain, swelling at the site of tube insertion, stoma infection and tube obstruction, whereas major complications including peritonitis, perforation, gastrointestinal bleeding, abdominal wall abscesses or sepsis can rarely happen [ 8 , 9 ]. In our case, the tube stoma site showed ischemic marks and pressure necrosis 1 week after PEG insertion, and the patient developed signs of sepsis which rapidly progressed to septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BBS is an unusual complication with an estimated incidence ranging from 0.3 to 2.4% [ 14 , 15 , 16 ]. It can be manifested with minor complications such as feeding intolerance, peristomal leak, pain, swelling at the site of tube insertion, stoma infection and tube obstruction, whereas major complications including peritonitis, perforation, gastrointestinal bleeding, abdominal wall abscesses or sepsis can rarely happen [ 8 , 9 ]. In our case, the tube stoma site showed ischemic marks and pressure necrosis 1 week after PEG insertion, and the patient developed signs of sepsis which rapidly progressed to septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The time of presentation of BBS varies in the literature; it is commonly expected to occur after 3 weeks to 3 months. Bhat et al [ 9 ] reported a case of early BBS which was managed with tube repositioning endoscopically as no other complications were present, and the authors explained it with severe retching and inadvertent pull during retching. Geer and Jeanmonod et al [ 14 ] observed a case with BBS 3 weeks after PEG tube insertion which was treated with endoscopic replacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are described cases of BBS as soon as 10 days after PEG placement [ 13 ]. In that situation the PEG tube can be salvaged and repositioned to the stomach without the need of replacement [ 14 ]. Although in our case BBS was recognized early, the orifice in the gastric wall was covered by fibrin and gastric mucosa; moreover, the internal bumper had migrated outside the gastric wall, so pulling the PEG tube back to the stomach using forceps or snare was impossible.…”
Section: Discussionmentioning
confidence: 99%